Evaluasi Luas Tambah Tanam (LTT) Padi Pada Program Swasembada Pangan di Kabupaten Sidoarjo - Arief Cahyo Widodo; Sri Juni Woro Astuti; Dwi Wahyu Prasetyono (FISIP UWP, 2020)
The development of the agricultural sector in order to increase rice production to ensure the availability of rice as the main food source is important and very strategic for the Indonesian people. The Strategy for Adding Planted Areas (LTT) for rice commodities carried out by the Government of Indonesia as well as improvements to irrigation infrastructure and agricultural machinery are strategic steps to optimize rice yields. The government is collaborating with Kodim 0816 Sidoarjo to optimize the achievement of the National Rice Self-Sufficiency target with the strategy of adding rice planting area. With the potential to reduce the amount of agricultural land in Sidoarjo Regency, it is hoped that it will not affect rice production and can even increase through the Rice Added Area (LTT) strategy. However, the existing strategy needs to be evaluated so that it can be more optimal in its implementation. The purpose of the study was to analyze the success of the strategy that had been carried out by the 0816/Sidoarjo Kodim and identify the factors that hindered the success of the Expanded Planting Area Program in the 0816 Sidoarjo Kodim area in increasing the assistance of the Special Effort Program (UPSUS) for Food Self-Sufficiency. This study uses a qualitative method, taking a case study of the 0816 Sidoarjo Kodim Special Efforts program in implementing the Rice Added Area (LTT) strategy in Sidoarjo Regency. The results of the study show that the area added-plant strategy has an impact on the achievement of the area-added-planting program in Sidoarjo Regency in the period 2014 – 2019 which is going well and shows increasing results every year. The inhibiting factor encountered at the beginning of the LTT strategy was the lack of coordination and collaboration between stakeholders, but after assistance from the 0816 Sidoarjo Kodim, which also acted as a liaison between related parties, the LTT strategy became more successful.